Lab experiments are a major source of knowledge in the social sciences - Armin Falk; James Joseph Heckman (Center for Economic Studies and ifo Institute (CESifo), 2009)
Laboratory experiments are a widely used methodology for advancing causal knowledge in the physical and life sciences. With the exception of psychology, the adoption of laboratory experiments has been much slower in the social sciences, although during the last two decades, the use of lab experiments has accelerated. Nonetheless, there remains considerable resistance among social scientists who argue that lab experiments lack `realism' and `generalizability'. In this article we discuss the advantages and limitations of laboratory social science experiments by comparing them to research based on non-experimental data and to field experiments. We argue that many recent objections against lab experiments are misguided and that even more lab experiments should be conducted.
Keywords: C90; C91; C92; C93; D00; 330; laboratory experiments; field experiments; controlled variation